Teachers’ Work Engagement, School Performance, and Teachers’ Retention in Selected Private Schools in the City Schools Division of Santa Rosa, Laguna - Gozon, Jennelyn P.; Yango, Antonio R. (Technium Social Sciences Journal, 2023)
Teacher work engagement was said to be influenced by motivation and other factors that lead to job satisfaction leading to teacher retention in an educational institution (Kamaruzaman et al., 2022). The goal of this study was to determine the teachers’ work engagement, school performance, and teachers’ retention. Likewise, this study probed the relationship between the respondents’ level of self-efficacy and well-being, level of self-efficacy and level of work engagement, and well-being and level of work engagement including the predictive ability of the level of work engagement, and level of school performance, taken singly or in combination, of the level of teachers’ retention of selected private secondary school teachers at City Schools Division of Santa Rosa, Laguna. The results showed that there was a multiple correlation between the respondents’ level of work engagement, level of school performance, and level of retention. A value of 0.000 indicated a high level of prediction of the independent variable (level of work engagement). The obtained R square of 0.597 showed that independent variables (level of work engagement and level of school performance) explain the variability of the dependent variable (retention level).